Cutting Processing and Experimental Verification of Epicycloid Bevel Gear based on Four-axis Linkage - Han Zhengyang; Deng Xiaozhong; Deng Jing; Zhang Mingzhu; Geng Longlong (Jixie chuandong, 2017)
The cutting principle of epicycloid bevel gears is analyzed,the operation mode and characteristics of five-axis with four-linkage epicycloid tooth bevel gear CNC machine are introduced,the feasibility of cutting epicycloid bevel gears based on the four-axis linkage is proposed and analyzed. The equivalent transformation for the processing mode of CNC machine and traditional mechanical machine is completed by analyzing the distinctions of mathematical models between the two kinds of machine. The tooth surface equation of the gear processed of the CNC machine is obtained. The relations among motion axes real-time motion coordinates are analyzed,and real-time coordinates of each motion axis of CNC machine are calculated. The ideal contact region is obtained by the gear cutting processing and rolling-inspection test. The correctness of the theory of cutting cycloid bevel gears based on four-axis linkage is verified and a theoretical support for the domestic independent research and development of spiral bevel gear processing equipment is provided.